2017
DOI: 10.1177/1354816617715159
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in the hospitality industry

Abstract: The hospitality industry is a rapidly growing revenue generator in many countries and is becoming economically important for generating employment and for integrating of immigrants into the labor market. As an industry where firms face fierce competition, it is important for the firms to maintain their competitiveness by distinguishing themselves from others through continuous improvements and innovations. In this article, we investigate the determinants of innovation in the hospitality industry by analyzing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 85 publications
(104 reference statements)
0
26
0
2
Order By: Relevance
“…The tourism industry is immersed in a market structure that is constantly changing, which is a consequence, among other factors, of the consumer's current demands for new tourism products and the introduction and widespread use of new information technologies in their creation, production, and consumption. In this uncertain environment, innovation processes are essential not only for generating, adapting, and implementing new ideas to solve problems, but also for creating new advantages that enable companies and destinations to be much more competitive and thus face the intense competition currently found in this sector [1][2][3][4]. On the other hand, innovation is one of the fundamental pillars for sustainable development, the fundamental objective of the tourism sector set by the UNWTO (World Tourism Organization) together with the UN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tourism industry is immersed in a market structure that is constantly changing, which is a consequence, among other factors, of the consumer's current demands for new tourism products and the introduction and widespread use of new information technologies in their creation, production, and consumption. In this uncertain environment, innovation processes are essential not only for generating, adapting, and implementing new ideas to solve problems, but also for creating new advantages that enable companies and destinations to be much more competitive and thus face the intense competition currently found in this sector [1][2][3][4]. On the other hand, innovation is one of the fundamental pillars for sustainable development, the fundamental objective of the tourism sector set by the UNWTO (World Tourism Organization) together with the UN.…”
Section: Introductionmentioning
confidence: 99%
“…According to Fagerberg & Verspagen [7], innovation is recognized as one of the most determining factors in the improvement of competitiveness, becoming a powerful explanatory factor of the and Communication Technology (ICT) for innovation generation: Jolly and Dimanche [42], Buhalis and Law [43]; Aldebert et al [44]; (3) the relationship between innovation and business performance: Martínez-Román et al [45], Lee et al [46]; (4) other studies focusing on various aspects of innovation and related issues in the hotel sector: Razumova et al [19] and Backman et al [2]; (5) the effect of ethical leadership on service innovative behavior: Dhar [21]; and (6) The influence of knowledge on marketing innovation and the effect of marketing innovation on the financial performance of hotels: Nieves and Díaz-Meneses [22].…”
Section: Introductionmentioning
confidence: 99%
“…The patenting behavior in the tourism sector has received little attention in the literature. This is surprising, given that tourism is known to be a highly innovative industry (Backman, Klaesson & Öner, ; Hjalager, ; Krizaj, Brodnik, & Bukovec, ; Martínez‐Román, Tamayo, Gamero, & Romero, ; Orfila‐Sintes, Crespì‐Cladera, & Martìnez‐Ros, ). Moreover, several studies emphasize that innovation in tourism is of primary importance for business performance and regional growth (Aldebert, Dang, & Longhi, ; Chen, ; Martínez‐López & Vargas‐Sánchez, ; Mattsson & Orfila‐Sintes, ; Randhawa, Kim, & Cichy, ; Tugores & García, ; Tugores & Valle, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have addressed the importance of stimulating various factors for the practice of innovation (Batle et al, 2018; Darroch, 2005; Li, 2014), while others have shown some advances in understanding the factors or barriers that determine favourable or unfavourable conditions of competitiveness for tourist destinations. Innovation practices are identified as an important tool for developing a company’s growth capacity and have been discussed at a variety of levels by academics and local policymakers rather than by regional and national policymakers (Backman et al, 2017; Farinha, et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%